Structure–5‐HT/D2 Receptor Affinity Relationship in a New Group of 1‐Arylpiperazynylalkyl Derivatives of 8‐Dialkylamino‐3, 7‐dimethyl‐1H‐purine‐2, 6(3H, 7H)‐dione. Issue 10 (11th August 2016) - Żmudzki, Paweł; Satała, Grzegorz; Chłoń‐Rzepa, Grażyna; Bojarski, Andrzej J.; Kazek, Grzegorz; Siwek, Agata; Gryboś, Anna; Głuch‐Lutwin, Monika; Wesołowska, Anna; Pawłowski, Maciej
Abstract : In our previous papers, we have reported that some 8‐amino‐1, 3‐dimethyl‐1 H ‐purine‐2, 6(3 H, 7 H )‐dione derivatives possessed high affinity and displayed agonistic, partial agonistic, or antagonistic activity for serotonin 5‐HT1A and dopamine D2 receptors. In order to examine further the influence of the substituent in the position 8 of the purine moiety and the influence of the xanthine core on the affinity for serotonin 5‐HT1A, 5‐HT2A, 5‐HT6, 5‐HT7, and dopamine D2 receptors, two series of 1‐arylpiperazynylalkyl derivatives of 8‐amino‐3, 7‐dimethyl‐1 H ‐purine‐2, 6(3 H, 7 H )‐dione were synthesized. All the final compounds were investigated in in vitro competition binding experiments for the serotonin 5‐HT1A, 5‐HT2A, 5‐HT6, 5‐HT7, and dopamine D2 receptors. The structure–affinity relationships for this group of compounds were discussed. For selected compounds, the functional assays for the 5‐HT1A and D2 receptors were carried out. The results of the assays indicated that these groups of derivatives possessed antagonistic activity for 5‐HT1A receptors and agonistic, partial agonistic, or antagonistic activity for D2 receptors. In total, 26 new compounds were synthesized, 20 of which were tested in in vitro binding experiments and 5 were tested in in vitro functional assays. Abstract : A series of 1‐arylpiperazinylalkyl derivatives of 8‐amino‐3, 7‐dimethyl‐1 H ‐purine‐2, 6(3 H, 7 H )‐dione were synthesized and investigated in in vitro competition binding experiments for the serotonin 5‐HT1A, 5‐HT2A, 5‐HT6, 5‐HT7, and dopamine D2 receptors. This group of derivatives possesses antagonist, partial agonist or agonist activity for these receptors.